-308G/A polymorphism of tumor necrosis factor alpha (TNF-α) gene and metabolic syndrome susceptibility: a meta-analysis - Dong Wang (Nature Portfolio, 2021)
Abstract Many studies tried to assess the relationship between -308G/A polymorphism of tumor necrosis factor alpha (TNF-α) gene and risk of metabolic syndrome (MS), but their results were contradictory. This meta-analysis aimed to precisely evaluate this association. A systematic literature search was performed in Pubmed database and WanFang Med Online, STATA software 14.0 was used for the meta-analysis. Eleven independent studies containing 3277 cases and 3312 controls were included in our meta-analysis. In overall analysis, significant association was found between -308G/A polymorphism of TNF-α and MS in both allele model (OR 1.47, 95% CI 1.09–1.98, P 0.013) and dominant model (OR 1.77, 95% CI 1.21–2.58, P 0.003). In the subgroup analysis, the A allele was associated with increased risk of MS in Asia group (allele model: OR 1.82 95% CI 1.31–2.53, P < 0.001; dominant model: OR 2.30, 95% CI 1.64–3.21 P < 0.001; homozygous model: OR 2.29, 95% CI 1.31–4.01, P 0.004), and decreased risk of MS in Europe group (dominant model: OR 0.83, 95% CI 0.70–0.99, P < 0.001; recessive model: OR 0.51, 95% CI 0.28–0.92, P 0.025; homozygous model: OR 0.49 95% CI 0.27–0.89, P 0.02). The A allele also appeared to linked to increased risk of MS in CDS group and IDF groups. No significant association was observed in NCEPATPIII group. Our results suggested that -308G/A of TNF-α gene was a risk factor for MS, but it may played different roles in different ethnics, further studies with larger sample size and more other ethnics should be performed to confirm our conclusions.